INVESTIGATIONS FOR STATISTICALLY CONTROLLED RESISTANCE SPOT WELDING SOLUTION OF STAINLESS STEEL (Journal of Mechanical Engineering, 2015)
The purpose of the present investigations is to study statistically controlled solution (from sensitization point of view) for 304 stainless steel (SS) joints using resistance spot welding process (RSWP). Starting from the parametric optimization of RSWP parameters (based upon Taguchi design), welded joints were prepared for functional checking. The output parameters selected for controlling the sensitization were hardness and tensile strength of welded joints. The results are supported by SEM analysis. Further the study suggests that the RSWP was found to be under statistical control (at optimized settings suggested by Taguchi design) as regard to sensitization of welded joint is concerned.